Warming Effects of Spring Rainfall Increase Methane Emissions From Thawing Permafrost - Rebecca B. Neumann; Colby J. Moorberg; Jessica D. Lundquist; Jesse C. Turner; Mark P. Waldrop; Jack W. McFarland; Eugenie S. Euskirchen; Colin W. Edgar; Merritt R. Turetsky (Geophysical Research Letters)
Abstract Methane emissions regulate the near‐term global warming potential of permafrost thaw, particularly where loss of ice‐rich permafrost converts forest and tundra into wetlands. Northern latitudes are expected to get warmer and wetter, and while there is consensus that warming will increase thaw and methane emissions, effects of increased precipitation are uncertain. At a thawing wetland complex in Interior Alaska, we found that interactions between rain and deep soil temperatures controlled methane emissions. In rainy years, recharge from the watershed rapidly altered wetland soil temperatures, warming the top ~80 cm of soil in spring and summer and cooling it in autumn. When soils were warmed by spring rainfall, methane emissions increased by ~30%. The warm, deep soils early in the growing season likely supported both microbial and plant processes that enhanced emissions. Our study identifies an important and unconsidered role of rain in governing the radiative forcing of thawing permafrost landscapes.